A prolonged, nationwide measles outbreak despite very high vaccination coverage in Israel, 2018-19. Issue 6 (December 2021) - Anis, Emilia; Haas, Eric J; Indenbaum, Viki; Singer, Sheperd Roee; Warshavsky, Bruce; Rishpon, Shmuel; Green, Manfred S; Mendelson, Ella; Grotto, Itamar; Kaliner, Ehud; Sadetzki, Siegal
Highlights: A major measles outbreak occurred in Israel in 2018-19 despite very high national vaccination coverage rates. Pockets of significant undervaccination and delayed vaccination were prevalent in communities with the highest incidence rates. Case importation was a key factor in causing and prolonging the outbreak. Effective control measures included vaccination information campaigns, mobile vaccination units, and a series of containment measures to minimize measles transmission. Summary Background: A major, prolonged measles outbreak occurred in Israel during 2018–19, despite vaccination coverage rates of 97% and 96% for the first and second doses, respectively, of measles containing vaccine (MCV). Aim: To study the causes and patterns of the outbreak through analysis of the epidemiological data, review the control measures taken, and identify lessons learned and efforts needed to prevent recurrences. Methods: All reported cases of measles in Israel from 1 March 2018 through 30 September 2019 were analysed using the epidemiological, clinical, laboratory, and demographic data that are systematically reported to the Division of Epidemiology of the Ministry of Health. Results: A total of 4, 311 measles cases were reported. 75% of case patients were children and 25% were adults. Pockets of undervaccination and delayed vaccination were identified: 72.6% of measles patients whose vaccination histories were known had not received any doses of MCV. Case importation was also a key factor, with a majority being adults coming from European countries and over half from Ukraine, a major locus of measles cases during the recent measles resurgence in Europe. Control measures were implemented at the local, district, and national levels. Conclusions: Similarities were noted between the 2018–19 outbreak and the prior one in 2007–08, principally pockets of undervaccination in the Jewish ultra-orthodox community, and case importation. Efforts to improve timeliness and coverage in pockets of undervaccination, and compliance with travel immunization guidelines, will be continued.